(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses some methods of teaching mathematics in science classes and methods of their application. The importance of using the necessary methods and methods in the process of solving problems and problems is revealed. The necessary tasks in teaching mathematics today and ways to solve them are described. It is known that the methods of teaching and creating knowledge in mathematics lessons in the working class are methods of continuous activity of teachers and students, and through this activity the acquisition of new knowledge, skills and abilities. The questions asked were designed to improve students’ thinking by forcing them to compare, contrast, activate or group events and facts, and make connections for them. To do this, it is necessary to approach the problem as a problem, pose the problem, find missing data and perform steps such as generating scientific hypotheses, hypotheses about bad and good situations, new knowledge about new knowledge. There are several types of knowledge creation methods. Students are offered sources of knowledge: oral, educational, practical methods, convenient ways to use them during the lesson.